Analysis of Carotenoid Pigment Types in the Carapace of the Male Crab Grapsus albolinetaus Latreille in Milbert 1812 - Mokoginta, Fatika Sari; Paransa, Darus Saadah Johanis; Kemer, Kurnati; Paulus, James J. H.; Kawung, Nickson J.; Manoppo, Henky (Sam Ratulangi University, 2021)
Carotenoid pigments have various colors such as yellow, orange, or red-orange. One of the carotenoid pigment sources is Crab G. albolineatus Latreille in Milbert 1812. Column chromatography separation technique was used to determine the metabolism of carotenoid pigments in the crab G. albolineatus latreille in Milbert 1812. This CC separation used hexane and acetone as the developer solution (70:30). The developer solution as known as the mobile phase is semipolar, while the stationary phase is silica powder G60. Therefore, it formed two metabolic pathways. The male G. albolineatus crab used in this study was on the D3 molting stage which had a concentration of 36.37 g/g dry residue and 4.72 g content. The types of pigments identified are: β – karoten, Zeaxanthin, lutein, β – kriptoxanthin dan Astaxanthin.Keywords: Carotenoid Pigments; G. albolineatus; Column Chromatography; MoltingAbstrakPigmen karotenoid memiliki berbagai warna seperti kuning, oranye, atau merah oranye. Salah satu sumber pigmen karotenoid adalah pada karapas kepiting G. albolineatus Latreille in Milbert 1812. Untuk mengetahui metabolisme jenis pigmen karotenoid pada kepiting Grapsus albolineatus latreille in Milbert 1812 yaitu menggunakan pemisahan kromatografi Kolom. Pemisahan KK ini menggunakan larutan pengembang heksan dan aseton (70:30). Larutan pengembang merupakan fase gerak yang bersifat semipolar dan fase diamnya menggunakan bubuk silika G60. Terbentuk dua jalur metabolisme. Kepiting G. albolineatus jantan yang digunakan pada penelitian berada di stadium molting D3 dengan konsentrasi sebesar 36,37 µg/g berat residu kering dan kandungan 4,72 µg. Jenis pigmen yang teridentifikasi yaitu : β – karoten, Zeaxanthin, lutein, β – kriptoxanthin dan Astaxanthin.Kata kunci: Pigmen; Karotenoid; G. albolineatus; Kromatofrafi Kolom; Molting